O acesso a dados bancários em investigações criminais federais: uma análise do cumprimento das Recomendações 9, 30 e 31 do grupo de ação financeira contra a lavagem de dinheiro e o financiamento do terrorismo - Vasconcelos, Felipe Torres (2022)
The combating the crime of money laundering requires the development of mechanisms for collecting and analyzing bank data, to track, freeze and recover assets arising from criminal activities. In 1990, the Financial Action Task Force (FATF) prepared a set of 40 recommendations, establishing an international standard for combating money laundering. The 2010 FATF report pointed out that Brazil would not compliance all the criteria of its Recommendations 9, 30 and 31. The content of these recommendations requires that bank secrecy does not inhibit the combating against money laundering and the financing of terrorism, ensuring that competent authorities should have the ability to expeditiously identify, track and freeze criminal assets, and powers to request records held by financial institutions in a timely manner. This Master's Thesis has as general objective to analyze the form and the period needed to access bank data in federal criminal investigations, in order to verify accomplishment by the Brazilian penal system to the content of the FATF Recommendations 9, 30 and 31. To achieve this objective, the research (i) describes the concept and characteristics of the money laundering and its relationship with the financial system; (ii) analyzes the concept and foundation of bank secrecy in Brazil; (iii) indicates ways to access financial information in federal criminal investigations; (iv) discusses the legal nature and content of FATF Recommendations 9, 30 and 31; and (v) analyzes the data from the Banking Movement Investigation System (SIMBA), created to digitalize the exchange of information between the Central Bank of Brazil (BCB), banking institutions, the Judiciary Branch, the Federal Police and the Federal Prosecutor`s Office. Based on SIMBA data, the research calculates the average and median of the time needed to access bank data in federal criminal investigations between 2010 and 2020. Regarding the methodology, the research adopts the monographic procedure, with a methodological objective exploratory and with bibliographic and documentary data collection technique. The calculation of the average and median results from the insertion of statistical formulas on the SIMBA data in Microsoft Excel software program. Thus, the research uses the auxiliary statistical method to analyze data from SIMBA. Based on the result of the quantitative and qualitative analysis of SIMBA data, the conclusion of this Master's Thesis indicates no integral compliance with FATF Recommendations 9, 30 and 31, due to the slowness and difficulty in obtaining financial data by the authorities in charge of criminal prosecution in Brazil.